Vaginoplasty and Fimbrioplasty on Vaginal Agenesis with Hematocolpos, Hematometra, and Hematosalpinx - Reswari, Arnova; Putri, Delima Istio Prawiradhani; Sasotya, RM Sonny (Jurnal Kesehatan Andalas, 2025)
Congenital vaginal agenesis is a rare abnormality of the female genital tract caused by abnormal embryological development of the Müllerian ducts. Clinical manifestations vary depending on the extent of the anomaly, severity, and the patient's age at presentation. It has been reported that a 16-year-old presented to the Urogynecology Clinic at Dr. Hasan Sadikin General Hospital, Bandung, with a chief complaint of cyclic abdominal pain that had been intermittent for the past 2 years and no history of menstruation. The patient was referred from several private hospitals with a history of previous exploratory laparotomies. The girl had normal secondary sexual development. No vaginal sac was found on pelvic examination. A hematocolpos measuring 10.08 x 6.80 x 6.02 cm and a hematometra measuring 14.41 x 12.92 x 10.62 cm were found on ultrasound. An exploratory laparotomy revealed bilateral hematosalpinx with a normal uterus. Vaginoplasty, bilateral partial salpingectomy, and bilateral fimbrioplasty were performed. In this case report, the authors successfully performed vaginoplasty and fimbrioplasty to evacuate the hematocolpos, hematometra, and hematosalpinx. Vaginal molding was then inserted into the neovaginal to prevent spontaneous vaginal collapse and maintained in situ for 2 weeks after surgery. Keywords:  hematocolpos, hematometra, hematosalpinx, vaginal agenesis